"Philosophical Values of Islamic Family Law towards the Mapaenre Botting and Mapparola Traditions in Bugis Community Weddings" - SARNAHKI SATTIA (Sipakainge: Inovasi Penelitian, Karya Ilmiah, dan Pengembangan (Islamic Science), 2023)
Marriage is a very important matter where marriage can form a household that is sakinah mawaddah warahmah, happy and prosperous. That is why marriage in Islam is highly recommended for those who can afford it. Husband and wife For the Bugis community, mappenre-botting is an activity of accompanying the groom to the bride's house to fulfill the marriage contract. In carrying out this ritual, the mappaenre bottling procession must take place before the sun reaches its peak. Mapparola is the bride's mutual visits to the groom's house. Implementation of mappa parola begins when the entire wedding procession is finished. Usually, the execution takes place a day or so after the wedding after consultation with both families. Formal events, such as weddings, the bride and groom sit in the aisle and take place during the day and usually continue into the evening. Keyword: Marriage,Mappaenre botting, Mapparola